Penambahan Pelet Trichoderma harzianum dalam Produksi Pupuk Organik Cair (POC) Limbah Tempe untuk Pertumbuhan Brassica juncea L. - Ike Apriani (Journal of Biotropical Research and Nature Technology, 2024)
Tempeh waste is obtained from the tempeh processing cycle in the form of liquid waste. This waste contains protein, fat, carbohydrates, and water. The nutrient content contained in the waste can be utilized by microorganisms for making POC. Effective Microorganisms (EM4) is one of the strong activators used for making POC. Trichoderma harzianum is known as a decomposer that can improve compost quality and soil structure. This study aims to determine whether the POC produced affects the growth of Brassica juncea L. The experiment used a completely randomized design (CRD) with 4 treatments, namely P0 (control), P1 (60 ml/L), P2 (120 ml/L) and P3 (180 ml/L). with a total of 24 experimental units. Analysis of NPK and C-Organic nutrient content showed Nitrogen = 0.20%, P = 0.060%, K = 0.24%, Organic C = 1.43%. P3 dose (180 ml/L) is the best dose in mustard green growth which includes observations of plant height, number of leaflets, leaf width, leaf area, mustard wet weight and mustard dry weight.